Efektivitas Triangle Pillow Kombinasi Virgin Coconut Oil (VCO) terhadap Pencegahan Pressure Ulcers pada Pasien Bed Rest di Ruang Intensive Care Unit (ICU) - Yindia Nungputria Hawati; Fitri Arofiati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Bed rest is when someone has to lie in bed for 24 hours each day. Bed rest has the potentially to cause pressure ulcers. Pressure ulcers are conditions caused by pressure combined with friction on bony areas. The implementation of triangle pillow combined with virgin coconut oil (VCO) intervention may be an alternative therapy to prevent pressure ulcers in bedridden patients. Objective: To determine the effectiveness of triangle pillow combined with virgin coconut oil (VCO) in preventing pressure ulcers in bedridden patients in the Intensive Care Unit (ICU). Methods: This study used a case report method with intervention using triangle pillow combined with virgin coconut oil (VCO) on bedridden patients in the ICU performed over 6 days in the morning after oral hygiene procedures and in the afternoon before the end of shift. This study used the Braden Scale instrument. Results: The results showed a change in the Braden scale from a high-risk scale of 9 to a moderate-risk scale of 14. Conclusion: The provision of triangle pillow combined with virgin coconut oil (VCO) is effective in preventing pressure ulcers in bedridden patients in the ICU.